2022
DOI: 10.3390/v14020323
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Delta Variant and Vaccination on the SARS-CoV-2 Viral Load

Abstract: Studies comparing SARS-CoV-2 nasopharyngeal (NP) viral load (VL) according to virus variant and host vaccination status have yielded inconsistent results. We conducted a single center prospective study between July and September 2021 at the drive-through testing center of the Toulouse University Hospital. We compared the NP VL of 3775 patients infected by the Delta (n = 3637) and Alpha (n = 138) variants, respectively. Patient’s symptoms and vaccination status (2619 unvaccinated, 636 one dose and 520 two doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Delta outpatients more frequently reported rhinorrhea, cough, and dyspnea compared to Omicron outpatients, who more frequently reported sore throat. This observation is in line with some other studies reporting more severe clinical presentation in Delta variant infections compared to the Omicron variant of SARS‐CoV‐2 24–28 . This study also reveals that Delta wave patients had significantly higher log RNA copies/µl in NPS and saliva compared to Omicron wave patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Delta outpatients more frequently reported rhinorrhea, cough, and dyspnea compared to Omicron outpatients, who more frequently reported sore throat. This observation is in line with some other studies reporting more severe clinical presentation in Delta variant infections compared to the Omicron variant of SARS‐CoV‐2 24–28 . This study also reveals that Delta wave patients had significantly higher log RNA copies/µl in NPS and saliva compared to Omicron wave patients.…”
Section: Discussionsupporting
confidence: 92%
“…This study also reveals that Delta wave patients had significantly higher log RNA copies/µl in NPS and saliva compared to Omicron wave patients. Genomic variant‐dependent NPS viral load observation is not unexpected; Migueres et al 28 showed higher viral loads in patients NPS infected with Delta compared to the Alpha variant, independent of patients’ age, sex, symptoms, and vaccination status. Interestingly, Salvagno et al 29 showed higher NPS viral loads in patients infected with the Omicron variant compared to patients infected with the Alpha variant.…”
Section: Discussionmentioning
confidence: 98%
“…1 ), as every genome transcription is accompanied by a likelihood of mutations. Since then and until October 5, 2021, the number of new variants relative to new isolates has decreased importantly; this may be due to the dominance of the Delta variant, increased sampling or, the most likely explanation, increasing vaccination 11 leading to reduced infection 12 , viral loads and fewer viral copies produced per infected individual 13 16 . This suggestion should be verified by a dedicated study of how vaccination is affecting realized mutation rates in the global population.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, changes that give rise to sufficiently different distributions of disease severity, such as those effected by some variants of concern, may inform parameters characterizing the variants. For example, the delta variant may cause overall higher viral loads 58 , which would lead to stronger immune activation on average, explaining the higher severity of this variant.…”
Section: Discussionmentioning
confidence: 99%